Kedudukan dan Fungsi Komisi Yudisial Republik Indonesia - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2011)
This article sum up that Judicial Commission (JC) in Indonesia has a strong position in the constitution, UUD 1945 (after amendment). Its JC‘s position is legally considered a similar position with The Supreme Court and Constitutional Court. In practice, however, its JC‘s function is less effective to be an external control against judges code of conduct.Three factors are involved to make the JC fails to establish control effectively. One is the decreasing integrity of the JC due to the fact that The Deputy of Chief was involved in bribery practice. Second, the weakness of leadership which set a side of the JC‘s core business, as an external control. The third, The Constitutional Court is decision led the JC‘s function to undermine its authority. In order to improve its effective control, it is necessary to attempt certain efforts. On the one hand, the JC is demanding not only to maintain its personal integrity, but also need to change a leadership system. More importantly, the JC capability to join collaboration in supporting government and legislative member in revising the bill No 24/2002 need to take into account.Key words : Judicial commission, judges code of conduct, and supreme court